ANALISIS GARIS SEMPADAN BANGUNAN (STUDI KASUS JALAN RAYA PAJAJARAN KOTA BOGOR) - Lucky Viasari; Prima Jiwa Osly (Jurnal Infrastruktur, 2017)
The development of the economic growth in Bogor increasing bring an impact for fulfillment will land and buildings in order to meet the activity of urban especially on highway Pajajaran Bogor which is found in the city center that will affect the spatial plans at every building and cause nonconformity border lines building particularly in the face of a building with local regulation applicable. Besides reducing aesthetic, it could also disrupt and endanger road users who will pass. This research is to analysis of border lines on buildings bylaws are being enacted. Data processing was done using software to ease in building determination of the limits of any buildings and the outer boundary of the road where next will be used to calculate long border lines building in every existing building and analyzed with local regulation applicable. The final result obtained that all building at case studies not according to rule regional government where the average building that violate is 14 % or by ± 16 yards from the middle of the road. Judging from the number of offense the authors provide recommendations that the existing changes in existing Regional Regulations in accordance with applicable policies.